Analysis of SEIQV Epidemic Model on the Spread of Covid-19 in Jember Regency - Alfarezi, Mohammad Rifqi; Hasan, Mohammad; Ubaidillah, Firdaus (Department of Matematics, Universitas Padjadjaran, 2024)
Covid-19 is a disease that attacks the respiratory system caused by infection with SARSCoV-2. Efforts to prevent the spread of Covid-19 by vaccination. The spread of disease can be modeled into a mathematical equation. The model used in this study is the SEIQV Model. The disease spread model is analyzed by finding the equilibrium point and the stability of the equilibrium point as well as the basic reproduction number. In the Covid-19 distribution model, a bifurcation analysis is carried out which is needed to determine changes in stability and changes in the number of equilibrium points. Then perform a numerical solution using the fourth-order Runge-Kutta method which is simulated using MATLAB.